Technical Assistance and Rural Extension: territorial strategies to promote family-based bee production in the backlands of Alagoas - João Rafael Gomes de Morais (Universidade Estadual de Alagoas, 2020)
Brazilian agricultural policy has a set of mechanisms for achieving its objectives.Regarding the contracting of Technical Assistance and Rural Extension (ATER) services, the federal government and state governments publish the Public Calls for Projects (CPPs) for calling and hiring governmental and non-governmental entities.Within this context, this article aims to report the process of elaborating the territorial project to promote honey production in the Territory of Batalha (AL) undertaken by Instituto HABITAR, in partnership with UNEAL, for submission to the FUNDECI 02 Notice / 2019 -Territorial Development published by Banco do Nordeste doBrasil (BNB). The research was supported by qualitative methodological procedures, such as document analysis, bibliographic survey and semi-structured interviews. It is hoped that this research will contribute to the enrichment of debates related to the promotion of beekeeping in the Northeastern semiarid, on the other hand, the study also aims to be a tool for approximation on the part students of social and agrarian sciences to the universe of ATER projects